2021
DOI: 10.1002/lsm.23371
|View full text |Cite
|
Sign up to set email alerts
|

High Contrast Reflectance Imaging of Enamel Demineralization and Remineralization at 1950‐nm for the Assessment of Lesion Activity

Abstract: Background and Objectives Previous studies have shown that large changes in the diffuse reflectivity of caries lesions during drying with air can be used to assess lesion activity. The largest changes occur at short wavelength infrared (SWIR) wavelengths coincident with high water absorption. The strongest water absorption in the SWIR occurs at 1950 nm. In this study changes in the reflectivity of simulated lesions with varying degrees of remineralization was measured at 1500–2340 nm and at 1950 nm as the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
1
13
1
1
Order By: Relevance
“…In this study, there was no significant difference in ΔI between the active and arrested lesions at 1950 nm or for most of the other wavelengths, with only 1300 nm showing a significant difference. This result conflicts with previous studies, including the recent study on bovine enamel blocks 21 where ΔI was significantly higher for active lesions. In this study, the lesions were chosen based on microCT data and are much deeper than the lesions that were chosen for previous investigation that utilized measurements with optical coherence tomography, which has a more limited imaging depth.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, there was no significant difference in ΔI between the active and arrested lesions at 1950 nm or for most of the other wavelengths, with only 1300 nm showing a significant difference. This result conflicts with previous studies, including the recent study on bovine enamel blocks 21 where ΔI was significantly higher for active lesions. In this study, the lesions were chosen based on microCT data and are much deeper than the lesions that were chosen for previous investigation that utilized measurements with optical coherence tomography, which has a more limited imaging depth.…”
Section: Discussioncontrasting
confidence: 99%
“…The high contrast of demineralization and the high sensitivity to water absorption suggests that 1950 nm should be ideal for SWIR reflectance dehydration measurements and recent studies of simulated lesions on bovine enamel blocks support this hypothesis. 21 That study also found that the change in contrast after drying (ΔI) was significantly higher at the 1950-nm broadband source than at other wavelengths in the 1500 to 2340-nm wavelength range. 21 The purpose of this study is to investigate the use of SWIR reflectance dehydration measurements at 1950 nm to assess the activity of naturally formed caries lesions on extracted teeth.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations